The Therapeutic Effects of Treadmill Exercise on Osteoarthritis in Rats by Inhibiting the HDAC3/NF-KappaB Pathway in vivo and in vitro - Zhang, He; Ji, Lu; Yang, Yue; Wei, Yingliang; Zhang, Xiaoning; Gang, Yi; Lu, Jinghan; Bai, Lunhao (Frontiers in Physiology, 2019)
Osteoarthritis (OA) is a disease characterized by non-bacterial inflammation. Histone deacetylase 3 (HDAC3) is a crucial positive regulator in the inflammation that leads to the development of non-OA inflammatory disease. However, the precise involvement of HDAC3 in OA is still unknown, and the underlying mechanism of exercise therapy in OA requires more research. We investigated the involvement of HDAC3 in exercise therapy-treated OA. Expression levels of HDAC3, a disintegrin and metalloproteinase with thrombospondin motifs-5 (ADAMTS-5), matrix metalloproteinase-13 (MMP-13), HDAC3 and nuclear factor-kappaB (NF-kappaB) were measured by western blotting, RT-PCR and immunohistochemistry. Cartilage damage and OA evaluation were measured by hematoxylin and eosin staining and Toluidine blue O staining according to the Mankin score and OARSI score, respectively. We found that moderate-intensity treadmill exercise could relieve OA. Meanwhile, the expression of HDAC3, MMP-13, ADAMTS-5 and NF-kappaB decreased, and collagen Ⅱ increased in the OA + moderate-intensity treadmill exercise group (OAM) compared with the OA group (OAG) or OA + high- or low-intensity treadmill exercise groups (OAH or OAL). Furthermore, we found the selective HDAC3 inhibitor RGFP966 could also alleviate inflammation in OA rat model through inhibition of nuclear translocation of NF-kappaB. To further explore the relationship between HDAC3 and NF-kappaB, we investigated the change of NF-kappaB relocation in IL-1β-treated chondrocytes under the stimulation of RGFP966. We found that RGFP966 could inhibit the expression of inflammatory markers of OA via regulation of HDAC3/NF-kappaB pathway. These investigations revealed that RGFP966 is therefore a promising new drug for treating OA.